Optimising immunogenicity with viral vectors: mixing MVA and HAdV-5 expressing the mycobacterial antigen Ag85A in a single injection - Betts, G; Poyntz, H; Stylianou, E; Reyes-Sandoval, A; Cottingham, M; Hill, A; McShane, H (Public Library of Science, 2012)
The Bacillus Calmette - Guerin (BCG) vaccine provides a critical but limited defense against Mycobacterium tuberculosis (M.tb). More than 60 years after the widespread introduction of BCG, there is an urgent need for a better vaccine. A large body of pre-clinical research continues to support ongoing clinical trials to assess whether viral vectors expressing M.tb antigens that are shared by BCG and M.tb, can be used alongside BCG to enhance protection. A major focus involves using multiple unique viral vectors to limit anti-vector immunity and thereby enhance responses to the insert antigen delivered. The successful introduction of viral vector vaccines to target M.tb and other pathogens will be reliant on reducing the costs when using multiple vectors and inhibiting the development of unwanted anti-vector responses that interfere with the response to insert antigen. This study examines methods to reduce the logistical costs of vaccination by mixing different viral vectors that share the same insert antigen in one vaccine; and whether combining different viral vectors reduces anti-vector immunity to improve immunogenicity to the insert antigen. Here we show that a homologous prime-boost regimen with a mixture of MVA (Modified Vaccinia virus Ankara) and Ad5 (human adenovirus type 5) vectors both expressing Ag85A in a single vaccine preparation is able to reduce anti-vector immunity, compared with a homologous prime-boost regimen with either vector alone. However, the level of immunogenicity induced by the homologous mixture remained comparable to that induced with single viral vectors and was less immunogenic than a heterologous Ad5 prime-MVA-boost regimen. These findings advance the understanding of how anti-vector immunity maybe reduced in viral vector vaccination regimens. Furthermore, an insight is provided to the impact on vaccine immunogenicity from altering vaccination methods to reduce the logistical demands of using separate vaccine preparations in the field.